PROGRAM PEMBIASAAN DALAM MENGUCAPKAN SALAM PADA ANAK TAMAN KANAK KANAK - achmadi, achmadi (Program Studi PG-PAUD Universitas PGRI Adi Buana Surabaya, 2019)
The habituation program is an icon of learning and forming good behavior for Early Childhood. The process ofperforming to behave good attitudes is given to early childhood by applying of norms in the society. Forexample